Necrotizing Fasciitis: An Aggressive Skin Condition-An Updated Overview, Diagnosis, Management, and Nursing Interventions - Alshammari, Sultan Sulaiman; Alshammari, Naif Khalaf Saeid; Alshammari, Mutariah Mishlah Lafi; Alshamriu, Alhunuf Mashi Alhumaydan; Alshammari, Sheemah Mishleh Lafi; Alshammry, Ahlam Muqbil Didan; Almutairi, Manal Manaja; Aljhoiny, Badria Eid; Almetehi, Wadyan Abdu Alrahman; Sohimanalshamre , Hamdah; Alshammary, Amal Mohammad; Alazmi, Jawaher Masoud Ali; et al. (Journal of Ecohumanism, 2024)
Background: Necrotizing fasciitis (NF) is a rapidly progressing soft tissue infection that causes extensive tissue destruction. Its polymicrobial etiology and association with comorbidities such as diabetes and alcoholism exacerbate its severity. Despite its rarity, NF carries high morbidity and mortality rates, necessitating immediate medical attention. Aim: This article provides an updated overview of NF, emphasizing diagnosis, management, and nursing interventions to improve patient outcomes. Methods: A comprehensive review of recent literature on NF's etiology, pathophysiology, diagnosis, and treatment strategies was conducted. This included examining clinical evaluation tools, imaging modalities, surgical procedures, and antimicrobial regimens. Nursing interventions, including patient monitoring and postoperative care, were also reviewed. Results: NF primarily involves gram-positive cocci, such as Staphylococcus aureus and Streptococcus species, but polymicrobial infections are common. Early diagnosis using tools like the Laboratory Risk Indicator for Necrotizing Infection (LRINEC) score and imaging significantly improves outcomes. Surgical debridement, aggressive antimicrobial therapy, and intensive care are critical components of treatment. Nursing interventions play a pivotal role in managing pain, ensuring nutritional support, and monitoring for complications. Conclusion: Early recognition and intervention in NF are essential for reducing morbidity and mortality. Comprehensive management requires multidisciplinary collaboration, with nurses playing a vital role in patient care and recovery. Future research should focus on refining diagnostic tools and treatment protocols to enhance outcomes.